Integrated Analysis of Climate Change Impacts and Adaptation Measures in Austrian Agriculture - Martin Schon̈hart; Hermine Mitter; Erwin Schmid; Georg Heinrich; Andreas Gobiet (German Journal of Agricultural Economics (GJAE), 2014)
An integrated modelling framework (IMF) has been developed and applied to analyse climate change impacts and the effectiveness of adaptation measures in Austrian agriculture. The IMF couples the crop rotation model CropRota, the bio-physical process model EPIC and the bottom-up economic land use model PASMA at regional level (NUTS-3) considering agrienvironmental indicators. Four contrasting regional climate model (RCM) simulations represent climate change until 2050. The RCM simulations are applied to a baseline and three adaptation and policy scenarios. Climate change increases crop productivity on national average in the IMF. Changes in average gross margins at national level range from 0% to +5% between the baseline and the three adaptation and policy scenarios. The impacts at NUTS-3 level range from -5% to +7% between the baseline and the three adaptation and policy scenarios. Adaptation measures such as planting of winter cover crops, reduced tillage and irrigation are effective in reducing yield losses, increasing revenues, or in improving environmental states under climate change. Future research should account for extreme weather events in order to analyse whether average productivity gains at the aggregated level suffice to cover costs from expected higher climate variability.
Keywords: 330